David Downton portraits of the world's most stylish women - Lacroix, Christian, 1951-; Von Teese, Dita, 1972- (Laurence King Publishing, 2015)
The first monograph on renowned fashion illustrator David Downton. With a Foreword by Christian Lacroix, and an Afterword by Dita Von Teese, this book showcases around 150 of David's drawings, featuring celebrities, actors, models, and fashion designers. The illustrations are enlivened by fascinating anecdotes revealing behind-the-scenes stories from the world of fashion. David recounts his inspirations, and specially commissioned photographs show him at work in his residence at Claridge's Hotel in London, where the great and good sit for his portraits.